S100A4 in Spinal Substantia Gelatinosa from Dorsal Root Ganglia Modulates Neuropathic Pain in a Rodent Spinal Nerve Injury Model - Jiang X; Zhao W; Zhao T; Yang M; Yuan H; Qian J; Xiang Z (Journal of Pain Research, 2021)
Xin Jiang,1,* Wenqi Zhao,1,* Tiantian Zhao,2,* Mei Yang,1 Hongbin Yuan,1 Jun Qian,2 Zhenghua Xiang3 1Department of Anesthesiology, Changzheng Hospital, Naval Medical University, Shanghai, People’s Republic of China; 2Department of General Surgery, Affiliated Xinchang Hospital of Shaoxing University, Zhejiang, People’s Republic of China; 3Department of Neurobiology, Key Laboratory of Molecular Neurobiology, Ministry of Education, Naval Medical University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhenghua XiangDepartment of Neurobiology, Key Laboratory of Molecular Neurobiology, Ministry of Education, Naval Medical University, No. 800 Xiangyin Road, Shanghai, 200433, People’s Republic of ChinaTel +86 21 81871044Fax +86 21 81885822Email xiang-zhenghua@163.comJun QianDepartment of General Surgery, Affiliated Xinchang Hospital of Shaoxing University, No. 117 Middle Gushan Road, Xinchang, Zhejiang, 312500, People’s Republic of ChinaTel +86 575 8638079Email qianj001@163.comPurpose: To detect the spatio-temporal expression of S100A4 in a spinal nerve ligation (SNL) rat model. Also to figure out which other molecules directly interact with S100A4 to explore the possible mechanisms which might be involved in neuropathic pain.Methods: Seven-week-old male SD rats were used for the SNL model construction. Immunofluorescence and Western blotting were used to detect the spatio-temporal expression of S100A4 in the model. S100A4 was co-labeled with a number of related molecules and marker molecules that can distinguish between cell types. After intrathecal injection of S100A4 neutralizing antibody, the behavioral changes of SNL rats were recorded, and molecular changes compared. The direct interaction between S100A4 and other related molecules was verified by co-immunoprecipitation (co-IP) to explore its possible mechanism.Results: After spinal nerve ligation, the content of S100A4 in the dorsal root ganglion (DRG) and spinal dorsal horn increased significantly. Intrathecal injection of S100A4 neutralizing antibody could effectively relieve the mechanical pain in rats. co-IP revealed a direct interaction between S100A4 and RAGE.Conclusion: The content of S100A4 in the DRG and spinal dorsal horn of SNL rats increased, compared with that of the control group. Intrathecal injection of S100A4 neutralizing antibody could effectively relieve the mechanical pain in SNL rats. S100A4 may be involved in the production of neuropathic pain through RAGE or other ways, but the specific mechanism needs to be further studied.Keywords: neuropathic pain, S100 calcium binding protein A4, receptor for advanced glycation end products, spinal nerve ligation model